Experimental analysis of a masonry façade subject to tunnelling-induced settlement - Giardina, Giorgia; Marini, Alessandra; Hendriks, Max A.N.; Rots, Jan G.; Rizzardini, Fabio; Giuriani, Ezio (Engineering structures, 2012)
► An experimental test on a 1/10th scaled masonry façade is performed. ► A tunnel induced settlement profile is applied. ► The soil–structure interaction is modelled by a well define interface. ► Amplification of vertical loads is used to reproduce the prototype stress field. ► Displacements, deformations, damage pattern and crack width evolution are monitored. The increase of tunnel excavations in urban areas calls for improved methods to assess the risk of damage on existing buildings. Laboratory tests performed in a controlled environment provide a better insight of the parameters governing the structural response and can be used as validation of computational models. This paper presents an experiment carried out on a 1/10th scaled masonry façade subject to tunnel induced settlement. The results demonstrate the determinant effects of soil structure interaction, presence of openings and brittle masonry cracking on the final damage, with crack width up to 6.3mm for a maximum applied settlement of 10mm.